The Performance of Venturi Microbubble Generator Type with a 60° Twisted Baffles - Fatma Roshanti; Sigit Deddy Purnomo Sidhi; Samsul Kamal; Deendarlianto; Indarto (Engineering Proceedings, 2023)
Due to their unique physical properties, microbubbles have received a lot of attention in waste treatment, aquaculture, and food processing. The demand for high-efficient and low power consumption microbubble generators has become a challenge today. Swirling flow has been widely proven to improve bubble formation. Numerous researchers have developed designs to produce swirl flow and strengthen the turbulence fluid flow. In this study, we present a swirl venturi microbubble generator with a 60° twisted baffle fin on the inlet section. The performance of the microbubble generator swirl venturi type was tested experimentally using parameters such as the distribution of bubble size, hydraulic power (Lw), and bubble-generating efficiency (ηb). A microbubble generator was installed in the transparent test pool with 672 L of water. A high-speed video camera was employed to visualize the flow behavior. The water and gas flow rates varied between 40 and 60 lpm and 0.1 and 0.5 lpm, respectively. The data were analyzed by MATLAB R2022b with the technique image processing method. The results showed that majority bubbles 100–300 µm were generated. An increased water flow rate (QL) will increase the hydraulic power by 22–27 W, while an enlargement of the gas flow rate (QG) would only enlarge it by 1 W. As the water flow rate increases, bubble-generating efficiency decreases. The lowest bubble-generating efficiency of 0.008% occurs at a QL 60 lpm and QG of 0.1 lpm. In conclusion, we can conclude that the microbubble generator swirl venturi type is an efficient device for generating microbubbles.